ASSESSMENT TECHNIQUES IN ENGLISH LANGUAGE EDUCATION (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Assessing proficiency in the English language is a crucial aspect of language education. It is part of the “Effective teaching, Effective learning, Effective Assessment” trio. Effective assessment techniques not only gauge students' language skills but also guide educators in tailoring instruction. This article explores various assessment techniques employed in English Language Education, emphasizing the significance of diverse methods for a comprehensive understanding of students' linguistic abilities.